2015
DOI: 10.1039/c5an01253h
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of insulin fibrillogenesis examined with ion mobility mass spectrometry and molecular modelling

Abstract: A prevalent type of protein misfolding causes the formation of β-sheet-rich structures known as amyloid fibrils. Research into the mechanisms of fibril formation has implications for both disease prevention and nanoscale templating technologies. This investigation into the aggregation of insulin utilises ion mobility mass spectrometry coupled with molecular modelling to identify and characterise oligomers formed during the 'lag' phase that precedes fibril growth. High resolution mass spectrometry and collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Prominent examples are epitope mapping utilising IM separation to identify antigen-epitope complexes [174][175][176] or fibril and amyloid formation. [177][178][179][180] Recent improvements in sample preparation (see Section 2) even allow the native IM-MS analysis of proteins from cell lysates. 21 The possibility of high-resolution native MS revolutionised the field of native MS and extended its applications enormously.…”
Section: Assessing Protein Shape and Stability Through Native Im-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples are epitope mapping utilising IM separation to identify antigen-epitope complexes [174][175][176] or fibril and amyloid formation. [177][178][179][180] Recent improvements in sample preparation (see Section 2) even allow the native IM-MS analysis of proteins from cell lysates. 21 The possibility of high-resolution native MS revolutionised the field of native MS and extended its applications enormously.…”
Section: Assessing Protein Shape and Stability Through Native Im-msmentioning
confidence: 99%
“…It ranges from building structural models to functional studies. Prominent examples are epitope mapping utilising IM separation to identify antigen‐epitope complexes 174–176 or fibril and amyloid formation 177–180 . Recent improvements in sample preparation (see Section 2) even allow the native IM‐MS analysis of proteins from cell lysates 21 …”
Section: Assessing Protein Shape and Stability Through Native Im‐msmentioning
confidence: 99%
“…Modern techniques enabling observation of fiber growth include atomic force microscopy (AFM), total internal reflection fluorescence microscopy (TIRFM), experiments that detect the growth of an ensemble of fibrils by surface plasmon resonance (SPR) or dynamic light scattering (DLS). Moreover, there are also techniques employing mass spectrometry (MS) coupled with high-performance liquid chromatography (HPLC) that monitor variations in concentration of the precursor protein as a determinant of incorporation during the fibers’ growth process [ 93 , 94 ]. An alternative approach to monitoring amyloid formation, enabling, among others, measurement of the kinetics of amyloid growth via real-time monitoring of increase in fiber mass, is based on QCM technology.…”
Section: Adsorption Of Peptide and Protein Molecules On The Qcm Sumentioning
confidence: 99%
“…[35][36][37] Numerous studies amyloid-related peptides and proteins demonstrated that ESI-IM-MS could provide unambiguous evidence for delineating the detailed mechanism of the aggregation process and assist in developing therapeutic agents and drug evaluation. [38][39][40] In this work, ESI-IM-MS was employed to observe the nature…”
Section: Introductionmentioning
confidence: 99%